2019
DOI: 10.1016/j.biochi.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of TMEM165 function in Golgi glycosylation and its Mn2+ sensitivity

Abstract: Since 2012, the interest for TMEM165 increased due to its implication in a rare genetic human disease named TMEM165-CDG (Congenital Disorder(s) of Glycosylation). TMEM165 is a Golgi localized protein, highly conserved through evolution and belonging to the uncharacterized protein family 0016 (UPF0016). Although the precise function of TMEM165 in glycosylation is still controversial, our results highly suggest that TMEM165 would act as a Golgi Ca2+/Mn2+ transporter regulating both Ca2+ and Mn2+ Golgi homeostasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 16 publications
5
23
0
Order By: Relevance
“…One of the possible mechanisms of transport with these three actors consists of a Ca 2+ -Mn 2+ /H + antiporter, where Ca 2+ and Mn 2+ would be transported at the Golgi level in one direction in exchange of protons. However, and in accordance with the limited and relatively indirect evidence of transport of protons, it was suggested that these UPF0016 members would work as Ca 2+ /Mn 2+ antiporters [ 23 , 29 ]. In A. thaliana , data from different studies led to the conclusion that Mn 2+ cations and, if transported, Ca 2+ cations would also be transported in the same direction, towards the chloroplast lumen [ 3 7 ], with indication of transport of protons only for PAM71 [ 3 ].…”
Section: The Upf0016 Family and Cation Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the possible mechanisms of transport with these three actors consists of a Ca 2+ -Mn 2+ /H + antiporter, where Ca 2+ and Mn 2+ would be transported at the Golgi level in one direction in exchange of protons. However, and in accordance with the limited and relatively indirect evidence of transport of protons, it was suggested that these UPF0016 members would work as Ca 2+ /Mn 2+ antiporters [ 23 , 29 ]. In A. thaliana , data from different studies led to the conclusion that Mn 2+ cations and, if transported, Ca 2+ cations would also be transported in the same direction, towards the chloroplast lumen [ 3 7 ], with indication of transport of protons only for PAM71 [ 3 ].…”
Section: The Upf0016 Family and Cation Transportmentioning
confidence: 99%
“…Nevertheless, based on data interpretation, the human and yeast orthologs TMEM165 and Gdt1p could transport Ca 2+ and Mn 2+ from the cytosol to the Golgi lumen in exchange of protons from the Golgi to the cytosol, if working as Ca 2+ -Mn 2+ /H + antiporters. In case of a Ca 2+ /Mn 2+ antiporter, data suggest that Mn 2+ would be imported in the Golgi in exchange of Ca 2+ [ 23 , 29 ]. In plants, Mn 2+ and, if transported, Ca 2+ would be transported from the cytosol to the stroma via CMT1, and then from the stroma to the thylakoid lumen via PAM71 [ 3 7 ].…”
Section: The Upf0016 Family and Cation Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data obtained in recent study give several indications of their implication in calcium and manganese homeostasis [47]. TM165 supplies Ca2+ and Mn2+ to the Golgi complex in exchange for H+ to sustain the functions of lactose synthase and potentially other glycosyltransferases [48,49]. The human Golgi protein TM165 can transport calcium and manganese in yeast and bacterial cells [50].…”
mentioning
confidence: 99%
“…Possible explanations include that TMEM165, a Golgi transmembrane protein and putative ion transporter, is acting as a Mn2+/Ca2+ transporter moving Mn2+ from the Golgi lumen to the cytosol. Evidence supports a role for TMEM165 in Mn++ transport as the TMEM165 protein is degraded by high cytosolic Mn2+ concentration [14,40]. In breast cancer, calcium ATPases are altered in expression levels and activity and these findings would further complicate the control of ion homeostasis [41,42].…”
Section: Discussionmentioning
confidence: 98%